Sky ladder by Cai Guo-Qiang, the construction of a happening - Gutiérrez Mora, Dolores (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2018)
This paper analyzes the artwork Sky ladder by the artist Cai Guo-Qiang, which took place in a small fishing island near the southeast coast of China. This is an artwork that unfolds within the territory. The staircase is an ephemeral structure, built to be burned, and a symbolic construction, which aims to connect the earth with the sky, following the most general of human aspirations. Throughout the analysis, three thematic lines are identified and established, which -through their relationship with other theoretical and practical references- are recognized as cultural theoretical vectors. These are the estrangement produced by the scalar contrast, the new forms of rooting present in the relationship of the artwork with the local community, and the uneven temporality that connects the past with the future through the instant. These vectors are deployed in the artwork in the form of happening, shedding light on contemporary territorial issues, and trying to point to modes of intervention that can serve as keys to architectural work.